Pengaruh Rasio Molar Dan Komposisi Katalis H-Zeolit Pada Pembuatan Plastisizer Dari Minyak Limbah Ikan Patin dengan Butanadiol - Sari, Novita Aprilia Maya; HS, Irdoni; Nirwana, Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Catfish waste can be processed into fat or fish oil that can be used as a source of raw material for plasticizers with the trans-esterification reaction. Transesterification reaction is a reaction between oils (triglycerides) with the alcohol that produces Fatty acid alkyl esters. Products that include the type of fatty acid alkyl ester is a plasticizer. Plasticizer additive compound that is added to hard or rigid resin can improve the flexibility and workability. In this study, the plasticizer is synthesized by transesterification of waste oil catfish and butanediol, using natural zeolite catalyst activated. The process is done with a variety of molar ratio (1: 2, 1: 4, and 1: 6) and H-zeolite catalyst composition (10%, 15%, and 20%) of waste oil based ikana catfish, with a fixed variable reaction temperature 145- 1500C, stirring speed of 200 rpm and reaction time of 6 hours. From the analysis of the results shows that the transesterification and the molar ratio of H-zeolite catalyst composition affects the conversion of the resulting product. The highest operating conditions obtained in this study is the molar ratio of 1: 4 and H-zeolite catalyst composition of 15% which resulted in the conversion reaction of 25.35%. Characteristics plasticizer generated in this study are Viscosity (200 C) 0.910 mPa.s and Specific Gravity (200 C) 0.918.   Keywords: Plasticizer, Trans-esterification, Waste Oil Catfish, Butanediol, H-Zeolite